Discursos étnico-raciais proferidos por candidatos/as a programa de ação afirmativa - Ferreira, Antônio Honório (2010)
This research articulates itself or gives continuity to dissertations and theses produced in the context of the Núcleo de Estudos de Gênero, Raça e Idade (NEGRI), part of the Program of Graduate Studies in social psychology from Pontifícia Universidade Católica de São Paulo/PUC-SP. Its overall goal, is to try to contribute to the understanding and the improvement of the ethnic-racial identification processes in affirmative action experiences. Its main specific goal is to describe and propose interpretations to the ethnic-racial speeches delivered in the International Fellowships Program - IFP (IFP Program) context. Based on the Munanga (1988), theoretical hypothesis, which proposes the plurality of being negro in Brazil; in the concept the concept of racism which integrates the structural and symbolic dimension in production of racial inequalities and in defense of the argument of social justice as the best justification, in Brazil, for the implementation of affirmative action policies with racial clipping, from Feres Júnior (2006). As a research method we adopted the Depth Hermeneutical (DH). In this thesis, the symbolic shapes examined comes from the answers given from candidates, which filled in a form to be part of the IFP Program, where the speeches were examined in specific fields related to self-declaration and racial identification, by content analysis technique. The profile from the authors which we analyzed the speech, shows that: proximity with the universe of candidates to the IFP Program; a predominant percentage of pretos and pardos authors, which have declared that they belong to the target group negro; with a predominance of young people and women. Among the 169 candidates that comprise our sample, 105 or 62.1% declared that they identify themselves as negros. High frequency occurred per source justification for self-declaration of color/race, suggesting the need for further studies. We found clear difference between subsets of authors which declared themselves as pretos or who identify themselves as negros and the authors as brancos. But the reports from the pardos show that they are located in the middle. The results reveal a variety of ways to present oneself as preto, pardo or branco in an affirmative action program with clipping ethnic-racial